IMPLEMENTASI PEMBELAJARAN LIFE SKILL DI SDIT NURUL FIKRI SIDOARJO - Mochammad Wildanu Mucholladun; Ainun Nadlif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The advancement of technology in the modern era brings new challenges for the world of education, including the demand on educational institutions to prepare students to be independent and ready to face the dynamics of modern life. Life Skills education becomes an important solution in shaping individuals who are able to adapt and compete in the midst of a complex society. This research aims to identify the content of life skills material and describe the implementation of its learning at SDIT Nurul Fikri Sidoarjo, which applies a full day school-based education model. The research approach used is qualitative with descriptive analysis methods. Data was collected through observation, interviews, and documentation, involving 4th-grade students, homeroom teachers, and the school principal as the main informants. Life Skills learning at this school covers the development of personal, social, intellectual, and vocational skills. The implementation of learning is carried out through a curriculum that is integrated with the daily activities of students. The research findings indicate that planning is a crucial stage in the implementation of Life Skill learning, considering that this curriculum is a unique feature of the school, independently developed by an internal team. The implementation of the program aligns with the initial plans, with materials adapted to each grade level, and several Life Skill activities integrated with other subjects to optimize time efficiency. Evaluation is conducted directly during the activities and is followed up with take-home assignments documented through photos, videos, and parental verification. This approach aims to ensure that Life Skill competencies continue to be practiced and applied by students in their home environment.